2020
DOI: 10.5435/jaaosglobal-d-20-00137
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Functional Outcomes After Elective Symptomatic Orthopaedic Implant Removal

Abstract: Introduction: The relative indications for removing symptomatic implants after osseous healing are not fully agreed on. The purpose of this study was to (1) determine whether patients showed improvement in functional outcomes after the removal of symptomatic orthopaedic implants, (2) compare the outcomes between upper and lower extremity implant removal, and (3) determine the rate of implant removal complications. Methods: A prospective study was conducted between 2013 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Williams et al assessed functional outcomes after IR in a study cohort of 85 patients and detected an improvement in function and ROM in 73% of the upper extremity, which is similar but higher than in our study [ 12 ]. Another study that investigated the outcome after IR of superior clavicle plates demonstrated a decrease in pain and an increase in mobilization in their case series [ 7 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Williams et al assessed functional outcomes after IR in a study cohort of 85 patients and detected an improvement in function and ROM in 73% of the upper extremity, which is similar but higher than in our study [ 12 ]. Another study that investigated the outcome after IR of superior clavicle plates demonstrated a decrease in pain and an increase in mobilization in their case series [ 7 ].…”
Section: Discussionsupporting
confidence: 73%
“…Williams et al described in their cohort of 119 patients a complication rate in 10%. Mostly, superficial infections were described [ 12 ]. In our study, three refractures (3.7%) were detected following IR at the clavicle and occurred within the first two weeks following IR.…”
Section: Discussionmentioning
confidence: 99%
“…However, other clinical studies have suggested hardware removal may improve function and reduce pain. 4,8,17,21,22 Cadaveric data has suggested that the removal of hardware consisting of epiphyseal screws placed in the setting of pediatric ankle fractures may decrease interarticular forces within the ankle. 3 Altering these forces may decrease the risk for subsequent joint degeneration or growth disturbances, and it is commonly cited as the rationale for elective hardware removal in pediatric ankle fractures.…”
Section: Introductionmentioning
confidence: 99%
“…5 Following the removal of symptomatic implants, patients frequently exhibit statistically significant improvement in function. 6,7 Despite the frequency of these procedures, the complication rates following the removal of implants have been reported to range from 3% to 40%, with almost a 10% complication rate in the largest series. 8 The time spent in the operating room is also unpredictable.…”
Section: Introductionmentioning
confidence: 99%